2012
DOI: 10.1007/s00396-012-2668-0
|View full text |Cite
|
Sign up to set email alerts
|

Photo-controlled/living radical polymerization mediated by 2,2,6,6-tetramethylpiperidine-1-oxyl in inert atmospheres

Abstract: The photo-controlled/living radical polymerization of methyl methacrylate using a nitroxide mediator was established in an inert atmosphere. The bulk polymerization was performed at room temperature using 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl as the mediator and (2RS,2′RS)-azobis(4-methoxy-2,4-dimethylvaleronitrile) as the initiator in the presence of (4-tert-butylphenyl)diphenylsulfonium triflate as the accelerator by irradiation with a high-pressure mercury lamp. The photopolymerization in a N 2 atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Yoshida reported the photo-CRP of various monomers accelerated by redox-active additives (e.g., iodonium salts, sulfonium salts, and iron–arene complex) with 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl (MTEMPO) at ambient temperature. The living nature of these systems was confirmed with kinetics studies; however, compared to traditional NMP methods, the dispersity indices of polymers obtained via these methods were typically higher. Nonetheless, the authors showed that the polymerization could be immediately stopped and restarted by turning the light source off and on for one cycle. , The authors suggested a unique mechanism wherein the additive accelerates the polymerization rate by reversibly oxidizing the nitroxide to an oxoaminium salt. Back electron transfer regenerates MTEMPO, which can then cap a propagating radical to reform a dormant chain.…”
Section: Photo-crp Via Direct Photochemical Processesmentioning
confidence: 99%
“…Yoshida reported the photo-CRP of various monomers accelerated by redox-active additives (e.g., iodonium salts, sulfonium salts, and iron–arene complex) with 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl (MTEMPO) at ambient temperature. The living nature of these systems was confirmed with kinetics studies; however, compared to traditional NMP methods, the dispersity indices of polymers obtained via these methods were typically higher. Nonetheless, the authors showed that the polymerization could be immediately stopped and restarted by turning the light source off and on for one cycle. , The authors suggested a unique mechanism wherein the additive accelerates the polymerization rate by reversibly oxidizing the nitroxide to an oxoaminium salt. Back electron transfer regenerates MTEMPO, which can then cap a propagating radical to reform a dormant chain.…”
Section: Photo-crp Via Direct Photochemical Processesmentioning
confidence: 99%
“…The ''living'' polymerization discussed here includes reversible deactivation radical polymerization (RDRP, also named as controlled/''living'' radical polymerization), ATRP (atom transfer radical polymerization), RAFT (reversible addition-fragmentation chain transfer polymerization), IMP (iodine mediated polymerization), CMRP (cobalt mediated radical polymerization), ROMP (ring-opening metathesis polymerization) and living cationic polymerization. Although nitroxide mediated photopolymerization [507][508][509][510][511][512][513][514][515][516] has been successfully developed, it will not be included as part of this review as it does not strictly follow a photoredox mechanism. In the cases of CMRP and IMP, current progress on both the energy transfer and electron transfer processes is covered.…”
Section: ''Living'' Polymerization By Photoredox Catalysismentioning
confidence: 99%
“…Until 2008, examples of photo-NMP had shown control only over initiation and not over propagation. The incorporation of photoredox additives (e.g., iodonium salts, sulfonium salts, and Fe–arene complexes) with TEMPO derivatives gave rise to photoswitchable NMP under irradiation with a 500 W high-pressure mercury lamp. These photoredox/TEMPO systems exhibit living polymerization activity and have been shown to control the propagation through the performance of one in situ on/off cycle. It is hypothesized that the photoredox additive enables polymerization control by reversibly oxidizing the nitroxide to an oxoaminium salt. …”
Section: Photochemical Controlmentioning
confidence: 99%